Analisis Tingkat Literasi terhadap Kesadaran Halal dan Penggunaan Produk Halal di Kabupaten Sambas - Andi Maryam; Sumar’in Sumar’in (IQTISHODUNA: Jurnal Ekonomi Islam, 2022)
Sambas Regency is a district that has the most extensive Muslim population distribution in West Kalimantan. This research took the research setting in Teluk Keramat District, one of the sub-districts in Sambas Regency, considering the distribution of the Muslim population. The percentage level of Muslims and non-Muslims is also the largest in Teluk Keramat District, reaching 97.30% of the population is Muslim. Teluk Keramat is a sub-district that is considered the "golden triangle" in the economic sector. This research uses an associative explanatory method or correlational study with a quantitative approach. The population in this study were all Muslim communities in the Teluk Keramat District, amounting to 72,470 people. This study found that the halal literacy variable will only have a significant positive effect on the use of halal products if it is through the halal awareness variable. In other words, halal literacy will have a significant positive impact in increasing the use of halal products if halal awareness is well established. But if Halal Literacy cannot increase halal awareness, then halal literacy will not significantly impact the use of halal products.